THE THERAPEUTIC EFFECT OF ADAPTOGENIC COMPLEX ON GUMS CONDITION DYNAMICS AND ORAL CAVITY COLONIZATION STABILITY IN CHRONIC CATARRHAL GINGIVITIS PATIENTS - V.V. Chereda; T.A. Petrushanko; H.A. Loban (Ukrainian Medical Stomatological Academy, 2016)
Physiological functions of destabilization, considerable mental stress, increased morbidity are typical for the initial period of training students, and lead to adaptation mechanisms disruption. Chronic catarrhal gingivitis is the leader in structure of periodontal diseases in young people. That's why it is to improve the treatments and evaluate its effectiveness.   The aim is to evaluate the effectiveness of chronic catarrhal gingivitis treatment in young people in terms of oral hygiene level, inflammation degree and mouth colonization resistance state. 23 chronic catarrhal gingivitis patients and students about 19-29 years of Higher State Educational Establishment of Ukraine "Ukrainian Medical Stomatological Academy" were examined in treatment dynamics. A generally accepted clinical oral cavity examination with the definition of CFE codes, hygienic Grenn-Vermilion (OHI-S) index, interdental hygienic index (HYG), PMA modification S.Parma, Muhlemann index, PBI index were performed. To assess the oral mucosa colonization resistance state the author's patent of Ukraine №51373 "The oral mucosa colonization resistance screening assessment" was used. Colonization resistance index (CRI) 1 point characterizes high colonization resistance level. CRI 0 points indicates the inhibition of colonization resistance barrier and reduce of normal microflora antagonistic properties. CRI 2 points are sign of the colonization barrier tension increase, quantitative increase of microorganisms, which may include not only symbiotic, but also opportunistic and pathogenic. The chronic catarrhal gingivitis treatment included agents that increase adverse external influences resistance, the regeneration of damaged tissue and gums inflammation, herbal adaptogen (Eleutherococcus) and vitamin A. Eleutherococcus administered internally daily 30 drops in 30 minutes before eating. Vitamin A 100,000 IU administered internally 1 per day after meals for 10 days. After 10 days of treatment hygienic Grenn-Vermilion index fell by 30.9%, indicating mouth hygienic condition improvement. Before treatment 87.0% of students had satisfactory hygiene, while 13.0% had unsatisfactory, on the 10-th day of treatment oral hygienic care in 52.2% of young people was good, 47.8 % - satisfactory. After 10 days of treatment a decrease of swelling complaints, gums bleeding, pain, inflammation inhibition were achieved in the study group. Lower PMA, Muhlemann and Muhlemann-Saxer (PBI) indexes, CFE by Leus confirm the periodontal lesions decrease under the treatment influence. All the patients with observed mouth colonization resistance inhibition, on the 10th day of treatment revealed increase of oral mucosa opportunistic and pathogenic microorganisms colonization resistance. Oral cavity microbial ecology changes served as a marker of the treatment effectiveness. The performed treatment increased resistance, vital functions, mental and psycho-emotional stress stability, functional adaptation abilities of organism. This is the effects of drugs that were used. The oral mucosa colonization resistance screening assessment method is a highly effective indicator system and an adequate criterion of the treatment effectiveness.